#1**+1 **

Do you mean \(2-x-2=4\)?

If so, I will solve it as so:

\(2-x-2=4\) | Combine the like terms on the left hand side of the equation |

\(-x=4\) | Divide by -1 on both sides to get rid of the negative on the x. |

\(x=-4\) | |

If you are ever unsure if you have the correct value for your unknown, just plug it back into the equation:

\(2-(-4)-2=4\) | Check to see if this is true; if it is wrong, you either made a mistake or you have an extraneous solution. |

\(2+4-2=4\) | Subtracting a negative number is the equivalent of adding a positive one. |

\(6-2=4\) | |

\(4=4\) | 4=4 is a true statement and concludes that the value for x is correct. |

TheXSquaredFactor
Jul 30, 2017